The Natural Suitability of Human Settlements and Their Spatial Differentiation in the Nenjiang River Basin, China - Zhao, Yang; Zhang, Junling (Frontiers in Environmental Science, 2022)
The natural suitability of human settlements (NSHS) of the Nenjiang River Basin was carried out by evaluation indices such as terrain characteristics, vegetation, hydrology, and climate of the region. The NSHS model is built using a GIS spatial analysis platform to reveal the suitability zoning and spatial differentiation (SD) characteristics of human settlements in the study area. The results show that the NSHS index of the study area ranges from 0.31 to 0.92, with an average of 0.54, indicating that the values show a gradual increase from northwest to southeast and from mountainous and hilly areas to plains. The most suitable and generally suitable areas constitute nearly 41.81% of the basin, and the population of these terrain accounts for about 84.25% of the total population of the basin. The suitable area category covers the largest area among all other categories accounting for about 25.16%, and the population of these regions accounts for about 12.46%. The critical suitable area category accounts for 21.70% of the basin, whereas unsuitable areas account for 11.32%, constituting the smallest areas compared to other categories. It is also evident that diverse limiting factors of NSHS characterize distinct areas in the study area. For example, high NSHS index, the normalized difference vegetation index (NDVI), and water resource index (WRI) are the main limiting factors in plane areas, low NSHS index, the relief degree of land surface (RDLS) index, and temperature-humidity index (THI) are the major limiting factors in the mountainous, hilly and plateau areas.